Assessment of knowledge, attitude and practices of generic drugs and their potential nocebo effects among second year medical students in a rural tertiary care teaching hospital: a cross-sectional study - Griglani, Diana L.; Patel, Nirav N.; Bhave, Amol L.; Bhavasar, Rahul P. (International Journal of Basic & Clinical Pharmacology, 2024)
Background: As drugs contribute significantly to healthcare costs, reduction in their cost by using generics offers a significant advantage so evaluation was done of knowledge, attitude, and practices of generic drugs and their potential nocebo effects among second year medical students in a tertiary care teaching hospital. Methods: A prospective, observational, and questionnaire-based study was conducted after approval by the Institutional Ethics Committee. Pretested and validated questionnaire consisting of 26 questions about generic drugs was filled by 92 participants. The filled questionnaires were collected and analyzed on Microsoft Excel sheet. Results: Majority (90.2%) students had heard about generic drugs, however, only 18.5% students thought there was a nocebo effect associated with the use of generic drugs. Majority of the study population had a positive attitude towards use of generic drugs and believed them to be equally efficacious as branded drugs in addition to not having more side effects than branded drugs, though their current practices did not reflect this knowledge and attitude. 63% also said that following this study, they were likely to prescribe or consume generics as future doctors and patients. Conclusions: The participants had sufficient knowledge and positive attitude towards use of generic drugs. Knowledge regarding the possible nocebo effects of generic drugs was lacking.